2021
DOI: 10.3389/fgeed.2021.752278
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Epigenetic Therapies for β-Thalassaemia by Altering the Expression of α-Globin Gene

Abstract: β-Thalassaemia is caused by over 300 mutations in and around the β-globin gene that lead to impaired synthesis of β-globin. The expression of α-globin continues normally, resulting in an excess of α-globin chains within red blood cells and their precursors. These unpaired α-globin chains form unstable α-hemichromes that trigger cascades of events to generate reactive oxygen species, leading to ineffective erythropoiesis and haemolysis in patients with β-thalassaemia. The clinical genetic data reported over sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 72 publications
0
10
0
Order By: Relevance
“…The accumulation of free α‐globin chains can be counteracted by decreasing α‐globin 54 or increasing the expression of γ‐globin and the production of fetal hemoglobin 55 . We demonstrated that BM Tfr2 deletion was associated with reduced mRNA levels of α‐globin, both as absolute value (Figure 3A), and as a ratio over the expression of the α‐hemoglobin stabilizing protein ( Ahsp , Figure S2G), a chaperone required to prevent the harmful aggregation of α‐globin 56,57 .…”
Section: Resultsmentioning
confidence: 99%
“…The accumulation of free α‐globin chains can be counteracted by decreasing α‐globin 54 or increasing the expression of γ‐globin and the production of fetal hemoglobin 55 . We demonstrated that BM Tfr2 deletion was associated with reduced mRNA levels of α‐globin, both as absolute value (Figure 3A), and as a ratio over the expression of the α‐hemoglobin stabilizing protein ( Ahsp , Figure S2G), a chaperone required to prevent the harmful aggregation of α‐globin 56,57 .…”
Section: Resultsmentioning
confidence: 99%
“…This is particularly true for a large proportion of patients living in poor and underdeveloped countries in South and Southeast Asia 22 . Most current research on therapeutics of thalassaemia have resulted in high-cost, technically demanding epigenetic and genetic-based therapies which would not be affordable to many at need 7 , 23 26 . Hence it is important to identify low-cost, easily accessible adjunct therapies that can either cure or ameliorate β-thalassaemia.…”
Section: Discussionmentioning
confidence: 99%
“…The second way to control the a gene expression through gene editing techniques involves affecting gene enhancers. It is considered that gene activity is mediated by 4 enhancers (MCS-R1 to R4), but among them MCS-R2 is the key element as researches show (39,41,42). According to an in vitro study, the deletion of MCS-R2 with CRISPR/Cas9 led to significant reductions in the a chains' levels: 60% in the case of monoallelic mutation and 90% if the deletion targeted both alleles of the enhancer (41,42).…”
Section: Genome Editing-based Treatmentsmentioning
confidence: 99%
“…It is considered that gene activity is mediated by 4 enhancers (MCS-R1 to R4), but among them MCS-R2 is the key element as researches show (39,41,42). According to an in vitro study, the deletion of MCS-R2 with CRISPR/Cas9 led to significant reductions in the a chains' levels: 60% in the case of monoallelic mutation and 90% if the deletion targeted both alleles of the enhancer (41,42). These results demonstrate the huge potential that gene therapy techniques have in the context of treating b thalassemia by modifying HBA activity and suggest the need for further investigations to study the concrete efficacy of these techniques.…”
Section: Genome Editing-based Treatmentsmentioning
confidence: 99%